Hospital Environmental Services and their Needs: Hospital Environmental Services and their Needs - Hasan, Sana (Pakistan Journal of Health Sciences, 2023)
Critically ill or seriously injured people visit Hospitals to seek care. Unfortunately, some patients end up with catching infection and suffering from another disease while they are hospitalized [1]. The Center for Disease Control (CDC) estimate that 687,000 patients every year, or one in every 31 hospital patients, develop an infection known as a healthcare-associated infection (HAI) [2]. An HAI is a type of infection that a patient contract while getting treatment in the hospital or an infection which was not there at the first place when the patient got admitted in the Hospital. These infections are tough to treat causing increase in the length of stay as well as they have financial implications too. These are antibiotic-resistant infections, and hospitals need to be watchful to avert the spread of such bacterial, fungal, and viral infections that cause HAIs. In order to combat these infections, a special type of cleaning processes is introduced in Healthcare generally known as Environmental Services. Hospital Environmental Services, or EVS, is the term in use to represent dedicated disinfecting and cleaning services accomplished by highly skilled technical workforce to impede the spread of HAIs in medical units and other Hospital areas. The Environmental Services staff in Hospital includes the cleaning staff, janitorial staff and Housekeeping Staff [3]. From absence of recognition of EVS contributions, in maintaining a clean and safe environment to a lack of training and resources while being obligated to take on apparently never-ending duties, EVS professionals have to traverse multifaceted trials every day while keeping in view the fact that how their everyday tasking can jeopardies their health. Despite their crucial role in averting infection, EVS staff always stay unappreciated and their jobs are unrewarding due to their apparent “low status” being placed at the lowest of the hospital employee hierarchy in terms of education and salary (as compared to other Hospital Staff) specially in LMICs like Pakistan [4]. This underlines the significance of small, pre-emptive gestures that coworkers can exercise to upsurge trust through different departments. To discontinue the pattern of social hierarchies and disassemble stereotypes, use of interpersonal maneuvers to increase social and emotive connections, can be emphasized to promote acknowledgment for EVS through deliberate appreciation initiatives [4]. There is lack of detailed Training Programs for EVS Staff at the Level of Universities and Colleges The teaching institutes should introduce such training programs, as well as relevant Hospital Departments should design short hands on certificate courses for their own staff too. The EVS Staff should have clear understanding of how to prevent themselves from infection and then how to prevent others from Infections. Their training and development courses should include details of communicable and non- communicable diseases, especially with reference to the routes of spread on infection. They should be equipped with knowledge about right cleaning agents, methods and disinfection and different types of contaminants. They should be trained to work in resource constraint environments. For example, they should have clear ideas about where use of gloves and other PPE is highly recommended and where it is not required. Similarly, which surfaces need to be cleaned and disinfected with what types of solutions and they should have a definite know how on dilutions [5]. They essentially have to perform accurate cleaning processes in different places in different times at hospitals (Isolation room, intensive care ward, operation room, wards, procedure room, reception room, delivery room, hospital lobby and stairways, offices, diner, kitchen, bathrooms). They should be sensitized with the alteration of cleaning plans as and when required. The experiences of EVS, who are indispensable but unacknowledged workers, can aid in shedding light on actionable insight for practical and policy changes directly. As the surge of HAIs continues to overwhelm hospitals, the healthcare delivery systems and interdisciplinary coworkers should identify staffing and resource strains for EVS. Implementation of Strategies that focus on appreciation and recognition for EVS through emotional support, native language education, provision of sufficient PPE supplies should be practiced as well as they should be offered enhanced reimbursements and wage [6].